An Unusual Case of Primary Cardiac Large B-cell Lymphoma Presenting as Cardiac Tamponade A in Chronically Immunosuppressed Patient - M, Daneshvar; Y, Khalid; L, Kaur; N, Dasu; P, Willard; S, Gabler (Cardiology and Cardiovascular Medicine, 2020)
A primary cardiac lymphoma (PCL) is an extremely rare form of a non-Hodgkin's lymphoma that involves the heart. It is a diffuse large B-cell lymphoma (DLBCL) that arises from the heart, pericardium, or both. Most PCLs are located in the right atrium. The mass alters the structure of the heart which creates electrical abnormalities. Pericardial involvement usually presents as dyspnea secondary to effusion [1]. We report a unique and rare case of an 82-year-old female who was on chronic immunosuppression for psoriatic arthritis that presented with shortness of breath secondary to cardiac tamponade requiring an emergent pericardial window. She was then diagnosed with primary cardiac lymphoma with primarily pericardial involvement. Subsequent cytology from the pericardial tissue and fluid revealed that she had stage 4 DLBCL. Finally, she developed recurrent pleural effusions in both lungs with rapid decompensation and respiratory failure which lead to death before further evaluation or treatment. Patients typically have a median survival of 7 months.